Menganalisis Neraca Pembayaran Sebagai Tolak Ukur Kemampuan Perekonomian Nasional Dalam Menopang Transaksi-transaksi Internasional - Ratna Sari Julaeha; Erlangga Samudra Utomo; Muhammad Yasin (Universitas Maritim AMNI Semarang, 2023)
The economy of a country can be seen from its internal conditions such as the real sector, namely production, consumption and investment. Then the monetary sector, such as inflation, the money supply and the balance of the exchange rate. In addition, the condition of the Indonesian economy can also be seen from external conditions which are reflected in the development of the balance of payments which illustrates the condition of the Indonesian economy in the real and monetary sectors. The balance of payments also measures the ability of the economy to support international transactions, especially transactions related to debt obligations and export-import transactions, and informs the government about the state of the economy, especially in this regard. On the results of economic relations with other countries. Thus, the balance of payments can assist in decision-making in the currency sector. Indonesia's balance of payments often fluctuates from time to time. A current account deficit does not result in a balance of payments deficit because the financial account increases capital and compensates for the current account deficit.